Effect of Different NPK Levels on Fodder Production of Sudan Grass (Sorghum bicolor var. Sudanese) - Singh, Shiv Raj; Singh, Manoj Kumar; Aakash; Meena, Kamlesh; Vishwakarma, S. P. (International Journal of Bio-resource and Stress Management, 2021)
A field experiment was conducted at R.G.S.C, Banaras Hindu University, Mirzapur, Uttar Pradesh, India during 2016 in kharif season (Sep.-Oct.) The aim was to evaluate the effect of different nitrogen, phosphorus and potassium level on fodder production of sudan grass (Sorghum bicolor var. Sudanese) for optimization of growth and yield, crude protein content and economics of sudan grass. The experimental was laid out in split plot design with four levels of nitrogen i.e. 60 kg N ha1, 80 kg N ha1, 100 kg N ha1 and 120 kg N ha-1 as main plot treatments and in the sub-plot three levels of phosphorus and potassium i.e. 30 kg P2O5+20 kg K2O ha-1, 40 kg P2O5+25 kg K2O ha-1 and 50 kg P2O5+30 kg K2O ha-1) were taken. The research findings revealed that application of nitrogen @ 120 kg ha-1 resulted maximum growth characters i.e. plant height (191.25 cm),number of leaf (8.02 plant-1), fresh weight (124.47 g plant-1), dry weight (21.10 g plant-1) and green fodder production (11455 kg ha-1), and as well as recorded maximum crude protein of sudan grass. The higher net return (Rs. 7920.32 ha1) was also recorded with nitrogen @ 120 kg ha-1 and in case of levels of phosphorus and potassium the application of 50 kg P2O5+30 kg K2O ha-1 enhanced the growth, yield, quality and economics of sudan grass.